Effect of Dietary Supplementation of Rumen Undegradable Protein on Productive Performance of Early Lactating Buffaloes - Tiwari, Shyam Krishna; Shah, Ramashish; Nepali, Dainik Bahadur; Tariq, Muhammad; Acharya, Krishna Prasad (Journal of Buffalo Science, 2019)
An experiment was conducted to study the effect of dietary supplementation of rumen un-degradable protein on productive performance of early lactating buffaloes for the duration of 90 days from February 5, 2014, to May 5, 2014. A total of twenty one lactating Murrah buffaloes in their early to mid-lactation were randomly selected and divided into three groups. Experimental diets were formulated into three- low (30.56% of dietary Crude Protein), medium (43.54% of dietary crude protein) and high (50.04% of dietary CP), iso-nitrogenous (16% CP) and iso-caloric (72% total digestible nutrients) rumen un-digestible protein (RUP) levels. A significant difference (p<0.05) in body weight gain of buffaloes was recorded in animals of high RUP group in comparison to medium and low RUP groups. Milk yield in the medium RUP group (43.54%) was significantly higher than the high and the low RUP group (p<0.05). The mean serum total protein, blood urea nitrogen concentrations were significantly lower in both the high and the medium RUP groups than in the low RUP group (p<0.05). However, blood glucose level was significantly higher in high RUP group than in low and medium RUP group (p<0.05) whereas milk fat, solid not fat, lactose, protein and electrical conductivity showed no significant differences among the three treatment groups (p>0.05). Hence, it can be concluded that the diet containing a medium level of dietary CP as RUP improved the productive performance of early lactating buffaloes. Thus, diet containing the medium level of dietary CP as RUP should be given to improve the productive performance of early lactating buffaloes under the climatic settings of Nepal.